Examining Indonesian College Students’ Behavioral Intention of Using Moodle App for E-Learning Platform - Siti Nur Azizah; Tono Suwartono; Sri Nurhayati; Endang Sungkawati; Nur'aeni Nur'aeni (Qubahan Academic Journal)
The Covid-19 crisis has forced educational institutions to conduct online learning. However, the technology readiness and acceptance of the human resource to this shift towards distance education via Learning Management System (LMS) remained in question. This is where the gap lies between the govt’s policy and LMS implementation reality. The current study aims to explore the Moodle LMS acceptance among undergraduate students throughout the Archipelago Indonesia during the pandemic and beyond by adopting a Unified Theory of Acceptance and Usage of Technologies (UTAUT) model to better explain the students' behavioral intentions. Data has been gathered from 510 undergraduate students via online questionnaire with the help of Google Form. We used adapted questionnaire and tried it out before being administered. Using the Partial Least Squares - Structural Equation Modelling to analyze the data, this study has found that the original UTAUT constructs, except for effort expectancy and facilitating conditions, can influence the intention of using the Moodle LMS. This study also has revealed that both computer self-efficacy and other-efficacy directly affect the intention of utilizing Moodle application for e-learning platform. Furthermore, experience positively moderated computer-self efficacy and negatively other-efficacy as hypothesized. The findings indicate that Performance Expectancy and Social Influences are confirmed to have contributed to UTAUT Model, while Effort Expectancy and Facilitating Condition are not. In addition, constructs within Social Cognitive Theory, i.e. Other Efficacy, Computer Self Efficacy and Behavioral Intention are totally confirmed both directly and indirectly.  With regard to the findings, practical recommendations have also been given at the end.